R[ex] S[ean] O’Fahey with the assistance of Hussein Ahmed, Lidwien Kapteijns, Mohamed M. Kassim, Jonathan Miran, Scott S. Reese and Ewald Wagner: Arabic Literature of Africa. Vol. III. Fascicle A: The Writings of the Muslim Peoples of Northeastern Africa - Weninger, Stefan (Aethiopica, 2005)
Review